Toward an AI-driven Islamic eco-campus model: bridging digital transformation and sustainability in Higher Education - Sulistiani, Dwi; Lestari, Yona Octiani; Kusuma, Yuanda (Proceeding of International Conference on Islamic Education (ICIED), 2025)
In today's digital era, the use of Artificial Intelligence (AI) has become a tool to assist human work, including in achieving sustainability performance in higher education. This study aims to describe the implementation, strategies, supporting factors, and inhibiting factors of AI use in supporting sustainability performance in higher education. This qualitative study took the case of a State Islamic University (UIN) A, which was ranked among the top 10 in the UI GreenMetric awards. Data were obtained through interviews, observations, and documentation. Semi-structured interviews were conducted with 10 informants, both online and offline, in mid-2025. Observations were obtained during campus visits. Documentation was obtained from the campus website, UI GreenMetric, and documents obtained from the green campus management. The research results show that UIN A has used AI to support its sustainability performance, especially in energy, transportation, infrastructure, waste management, and education. Commitment from the leadership, solid team support, and financial support are important supporting factors in the success of sustainability performance on campus. Although there are still obstacles such as limited human resource competency in AI, data security, and limited integration of AI and existing systems on campus. This research provides a theoretical contribution in the development of the triple bottom line theory which is integrated with Islamic values, thus becoming the quadrant bottom line theory. The results of this study can also provide empirical evidence of campus support for sustainability issues. However, there are still many improvements and enhancements that need to be made by green campus management to provide maximum support for the Sustainability Development Goals (SDGs).